Ecological inspirations for the Tourism Area Life Cycle (TALC) model - Szeligiewicz, Wojciech (Studia Ecologiae et Bioethicae, 2020)
Richard Butler’s Tourism Area Life Cycle (TALC) model proposes a specified view on the qualitative changes in the number of tourists N in the area over time and the environmental, social and economic processes taking place there simultaneously. N changes follow S-shaped curve up to stagnation phase. Such a course was adopted in the TALC model, assuming that the tourist population at this stage develops in accordance with a logistic model derived from ecology. This work aimed to recall the properties of the logistic model and the ecological assumptions underlying it, and some of the consequences of incorporating the logistic model into the TALC model. An attempt has also been made to link other TALC aspects with ecology. In particular, reference is made to the graph on the right side of the logistic equation of the TALC model as a function of N with the phases of evolution of the tourist area marked, which reminds that the most attractive area is the original area, i.e. when N is small, as it is characterized by the highest per capita growth of the tourist population. According to this figure, as N increases, there is a linear decrease in attractiveness despite the investments introduced according to the TALC model scenario, i.e. they do not reverse this trend. The same diagram can be used to show some elementary differences between ecotourism and mass tourism. The issues of population regulation were also raised, including the density-dependent self-regulation, the Allee effect, the concept of environmental capacity and r and K strategies. It was also pointed out that the experience gained in the field of population modelling in ecology could help to model tourist populations.